Pengaruh Problem Based Learning Terhadap Kemampuan Memecahkan Masalah Peserta Didik - Khadijah, Ifah; Nurhadi, M Wiran Jaya; Wijaya, Andri; Baiturrahman, Ridwan; Azahra, Khalida Zia Fitrah; Hambali, M Syahbani (Penerbit Widina, Widina Media Utama, 2025)
This study aims to determine the effect of implementing the Problem Based Learning (PBL) model on students' ability to solve problems in the Aqidah Akhlak learning at madrasah schools. The PBL approach is implemented through steps such as providing authentic problems, group discussions, independent research, collaboration, and solution presentations, which have proven to enhance students' analytical skills, critical thinking, as well as their sense of responsibility and active participation. The research method used is qualitative descriptive with techniques such as in-depth interviews, direct observations, and documentation studies involving students and teachers during the learning process. The results show that the implementation of PBL significantly enhances students' problem-solving abilities and learning motivation, as well as enriches learning experiences relevant to the context of social and religious life. The main challenges faced include the significant time required for preparation and implementation, as well as the need for students to have a deep understanding of the stages of PBL. The conclusion of this study emphasizes that PBL is an effective learning innovation in enhancing students' competencies and supporting the development of character and 21st-century skills, making it worthy of broader development with support from all stakeholders.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penerapan model Problem Based Learning (PBL) terhadap kemampuan peserta didik dalam memecahkan masalah dalam pembelajaran Aqidah Akhlak di sekolah madrasah. Pendekatan PBL diterapkan melalui langkah-langkah seperti pemberian masalah autentik, diskusi kelompok, penelitian mandiri, kolaborasi, dan presentasi solusi, yang terbukti mampu meningkatkan kemampuan analisis, berpikir kritis, serta sikap bertanggung jawab dan aktif siswa. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik wawancara mendalam, observasi langsung, dan studi dokumentasi kepada peserta didik dan guru selama proses pembelajaran. Hasil menunjukkan bahwa penerapan PBL secara signifikan meningkatkan kemampuan pemecahan masalah dan motivasi belajar siswa, serta memperkaya pengalaman belajar yang relevan dengan konteks kehidupan sosial dan keagamaan. Kendala utama yang dihadapi meliputi waktu persiapan dan pelaksanaan yang cukup besar, serta perlunya pemahaman mendalam dari peserta didik terhadap tahapan-tahapan PBL. Kesimpulan dari penelitian ini menegaskan bahwa PBL merupakan inovasi pembelajaran yang efektif dalam meningkatkan kompetensi peserta didik dan mendukung pengembangan karakter serta keahlian abad ke-21, sehingga layak dikembangkan secara lebih luas dengan dukungan dari seluruh pemangku kepentingan.